Prevalence of Diseases and Observation of Drug Utilization Pattern in Elderly Patients: A Home Medication Review - P, Awanish; Tripathi, Poonam; DP, Rishabh (Indian Journal of Pharmacy Practice)
Medication related risk factors and their effect on health outcomes in geriatric patients remains unclear, which can only be identified by home visits. Therefore in the present study door to door survey was conducted in an area of 2 sq. km surrounding Shri Mahant Indiresh Hospital of Dehradun to determine drug utilization pattern and prevalence of chronic diseases in elderly by visiting them in their community. The study was primarily targeted at the elderly because, as a group they take more drugs than their younger counterparts and are known to be at risk of the side effects of many of the drugs they consume. The study shows that Cardiac disorders (34%) were most prevalent among elderly population. 40% patients were non-compliant due to poor economic status, difficulty in swallowing of the prescribed dosage forms, and disturbing side effects. The study also shows that Self-medication (38%) was a prevalent phenomenon among the elderly. 20% patients suffered from side effects of the drug were advised either to reduce their dosage regimen or to visit their physician with a request for an alternate medicine. Present study concludes that a home medication review greatly decreases the load on tertiary care services for the elderly, which in India are sadly lacking. This may be because the Indian elderly at present are mostly in the “young elderly” age group (60 to 75 yrs old) in which there is little demand for long term health care
Keywords: Home medication review; Selfmedication; Geriatrics; and Polypharmacy